Energy effects of non-energy policies: Minimum wage standard and enterprise energy efficiency in China. (December 2022) - Zhao, Yueyang; Mao, Jinzhou
Abstract: Improving energy efficiency is one of the core goals of energy policy, but non-energy policies also play a role that cannot be ignored. To explore the energy effects of nonenergy policies on the production sector, this paper studies the effect of minimum wage on the energy efficiency of enterprises based on China's 2000–2009 minimum wage data and industrial enterprise microdata. We find that the minimum wage standard significantly improves the energy efficiency of enterprises. This conclusion holds after addressing a series of endogeneity concerns. The channel analyses verify that the minimum wage standard strengthens the allocation of the fixed assets of enterprises, improves innovation ability, and thus promotes energy efficiency. Furthermore, the energy efficiency improvements due to the minimum wage standard are more prominent in nonstate-owned enterprises, enterprises with few financing constraints and labour-intensive enterprises. Additionally, energy efficiency improvement helps alleviate the adverse impact of industrial enterprises on the ecological environment. The research conclusion of this paper shows that the government can optimize the allocation of resources through administrative ways and promote the efficient use of energy and the recovery of green industries. Highlights: This paper studies the influencing factors of energy efficiency from the micro-enterprise level. The impact mechanism of the minimum wage standard on the energy efficiency of enterprises is clarified. There is heterogeneity in the impact of the minimum wage standard on the energy efficiency of enterprises. Improvements in energy efficiency can mitigate the negative impact of industrial enterprises on the environment.